Analisis Penyelesaian Sengketa Kontrak Lisan di UMKM Kampung Sukadana Perspektif Hukum Ekonomi Syariah - Rohman, Rizal Fathu; Hidayah, Phani Annisatul (Ma'soem University, 2025)
This study examines the practice of oral employment contracts and dispute-resolution mechanisms in the MSME sector of Kampung Sukadana through the perspectives of Positive Law and Islamic Economic Law. Oral contracts remain the primary choice due to practical considerations and close familial relations; however, the absence of written evidence weakens legal protection for both workers and employers. The research employs a qualitative approach with an empirical juridical design, involving seven micro-enterprise actors through observation and in-depth interviews. The findings indicate that oral contracts are legally valid under positive law but carry evidentiary weaknesses, while in Islamic law they are permissible as long as they do not involve elements of gharar, with written documentation being recommended to prevent disputes. Dispute resolution is carried out through deliberation (sulh) and arbitration (tahkim), which align with local familial values and the principles of Islamic law. These findings highlight the need for integrating formal law, local wisdom, and Islamic values to ensure justice and legal certainty within the MSME sector.